Design of rotational potential in a phenyltriptycene molecular rotor by exploiting CH/π-interaction between tripticil hydrogen and phenyl. Issue 35 (30th August 2022) - Inami, Hazuki; Inagaki, Yusuke; Setaka, Wataru
Abstract : Design of the relative energies among three rotamers of a substituted phenyltriptycene by exploiting the CH/π-interaction was achieved. Abstract : The chemistry of artificial molecular rotors has recently attracted considerable attention in the field of molecular machines. Phenyltriptycene could be used as a stepwise molecular rotor because it is composed of a phenyl rotor and a triptycene stator, in which the rotational potential can be designed by introducing substituents. In this study, a novel design of the relative energies among three rotamers of a substituted phenyltriptycene by exploiting the CH/π-interaction between a peri -hydrogen and phenyl was investigated. First, the structures of two different phenyltriptycenes were compared to confirm CH/π-interactions. Second, the effects of the substituents of 1, 4, 5-trichloro-3′, 5′-dimethoxyphenyltriptycene on the relative energies were investigated by structural analysis, temperature-dependent nuclear magnetic resonance studies, and density functional theory calculations. The obtained results should facilitate the design of novel molecular switches and/or molecular rotors.